Ritual, superstition and science in wound healing: Part 2 -- the role of superstition and ritual in the interpretation of wound aetiology and treatment across cultures. - Wynn, Matthew (Wounds UK, 2025)
This article explores the enduring role of superstitious beliefs in the interpretation and treatment of wounds across different cultures despite advancements in medical science. Ethnographic studies from Cameroon, Ghana, Nigeria and Sweden reveal that traditional and superstitious beliefs often coexist with biomedical practices. In Ghana, chronic wounds are frequently attributed to supernatural causes and treated with traditional methods, while in Sweden, Muslim migrant populations may accept the value of medical advice but view long-term outcomes as the will of Allah. This article highlights the influence of cultural traditions, knowledge deficits, and the limitations of scientific approaches in fully addressing patient needs. It discusses the persistence of ritualistic practices among healthcare providers in relation to wounds and the potential implications, such as the need for enhanced education, improved diagnostic tools, and culturally sensitive communication, to bridge the gap between traditional beliefs and evidence-based practices in wound care. The article underscores the importance of interdisciplinary collaboration and patient-centred care to improve outcomes in wound treatment.